Formulation of ceramics feedstock for low pressure injection moulding - Tan, Jia Hui (2021)
Injection moulding is a standard manufacturing process in the industry, where it can be categorized into low pressure injection moulding (LPIM) and high pressure injection moulding (HPIM). LPIM is a manufacturing process similar to the additive manufacturing process, direct ink writing (DIW), as both processes, require low pressure to force the feedstock out of the nozzle. The main objective of this study is to formulate a suitable composition of binderceramic feedstock for LPIM. The ceramic feedstock applied is kaolin clay with the addition of binders: carboxy methylcellulose (CMC), hydroxypropyl methylcellulose (HPMC), methylcellulose (MC), and a dispersant, polyacrylic acid (PAA). First, the clay and binders ratio was tested multiple times to obtain the suitable output during the LPIM process using a 3D-printed syringe pump extruder, the injection moulding test. Then, the same clay tested in the injection moulding test proceeded for the weight test; it was discovered that the maximum weight to enable a complete extruded sample is 6 kgf (58.86 N). As a result, the optimum mass fraction is 65 wt%, 6 wt%, 3 wt%, and 26 wt% for kaolin, binder, dispersant, and water, respectively; the three sets of clay can be extruded entirely into the mould and still maintains their shape. The samples with the optimum composition have proceeded for debinding and sintering process where Sample A, B and C are using binders CMC, HPMC and MC, respectively. After sintered, the shrinkage of samples was investigated, it was found that Sample A has a shrinkage of 55.80 % and Samples B and C both have a shrinkage of 51.79 %. In the XRD analysis, the spectra of the sintered samples match with the spectra of mullite and coesite.